Cloud computing with Amazon Web Services video sneak peek - Golden, Bernard; Noa, Jorge; Safari eBooks ([S.l.] : Addison-Wesley Professional, 2010)
"Cloud computing expert Bernard Golden provides easy-to-follow instructions that will allow developers to get up and running with the Amazon Web Services platform in no time. This video covers three key elements of working with AWS: (1) Creating, launching, and shutting down EC2 instances; (2) Storage and persistence in AWS environments; and (3) managing AWS-based instances and managing applications in AWS environments. Further, this video provides a set of best practices for working with S3, Elastic Book Store, and SimpleDB. This is a Sneak Peek preview version of the Cloud Computing with Amazon Web Services Video"--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Description from resource description page (viewed Sept. 30, 2010).
Keywords: Cloud computing; Web services; Electronic data processing -- Distributed processing; Amazon.com (Firm); Electronic books